SEGMENTASI WISATAWAN DI MEDIA SOSIAL BERBASIS KLASTER: BAGAIMANA WISATAWAN BERINTERAKSI DENGAN KONTEN PERJALANAN WISATA? - Maheswari, Aulia Dinda; Setiyorini, Heri Puspito Diyah; Khaerani, Rijal (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractSocial media plays a critical role in modern destination marketing, as individuals increasingly rely on these platforms to guide their travel decisions. This study segments tourists based on their interactions with social media, offering insights to help stakeholders in the tourism industry develop more efficient marketing strategies. Using the Stimulus-Organism-Response (S-O-R) theory, the research examines variables such as online atmospherics, perceived usefulness, perceived enjoyment, flow experience, attitude, revisit intention, and further usage intention. A questionnaire-based survey was conducted with 400 respondents, primarily college students. Data were analyzed using factor-cluster analysis, including Principal Component Analysis (PCA) and K-Means clustering. The findings identified four key social media interaction factors: immersive, future trip scouting, destination desire, and happy scroll moments. Additionally, five tourist segments emerged: joyful exploration, destination appeal, travel visioning, captivating, and combination. This study enhances the S-O-R theory, particularly its organism component, by providing insights into how social media interactions influence tourist market segmentation. The results offer practical guidance for destination managers to refine content creation strategies and improve marketing effectiveness by addressing the factors and segments identified in this research.Keywords: Tourist Segmentation; Social Media; Cluster Analysis; SOR Theory  AbstrakMedia sosial memainkan peran penting dalam pemasaran destinasi modern, karena individu semakin bergantung pada platform ini untuk memandu keputusan perjalanan mereka. Studi ini mengelompokkan wisatawan berdasarkan interaksi mereka dengan media sosial, menawarkan wawasan untuk membantu pemangku kepentingan di industri pariwisata mengembangkan strategi pemasaran yang lebih efisien. Dengan menggunakan teori Stimulus-Organism-Response (S-O-R), penelitian ini menguji variabel-variabel seperti online atmospherics, perceived usefulness, perceived enjoyment, flow experience, attitude, revisit intention, dan further usage intention. Survei berbasis kuesioner dilakukan terhadap 400 responden, terutama mahasiswa. Data dianalisis menggunakan analisis faktor-klaster, termasuk Principal Component Analysis (PCA) dan K-Means. Temuan ini mengidentifikasi empat faktor utama interaksi pada media sosial: immersive, future trip scouting, destination desire, dan happy scroll moment. Selain itu, lima segmen wisata muncul: joyful exploration, destination appeal, travel visioning, captivating, dan combination. Studi ini menyempurnakan teori S-O-R, khususnya komponen organisme, dengan memberikan wawasan tentang bagaimana interaksi media sosial mempengaruhi segmentasi pasar wisatawan. Hasilnya menawarkan panduan praktis bagi pengelola destinasi untuk menyempurnakan strategi pembuatan konten dan meningkatkan efektivitas pemasaran dengan mengatasi faktor dan segmen yang diidentifikasi dalam penelitian ini.Kata Kunci : Segmentasi Wisatawan; Media Sosial; Analisis Kluster; Teori SOR